BUILDING WINNING STRATEGY FOR COMPETITIVE PERFORMANCE THROUGH CORPORATE SOCIAL RESPONSIBILITY: AN X-RAY OF MTN NIGERIA - Sunday Abayomi, ADEBISI; Taiwo, AKINMADELO (Strategii Manageriale, 2014)
This research was undertaken by the authors with the primary objective of appraising the possibility of organization leveraging on Corporate Social Responsibilities (CSR) as strategic tool for competitive performance with particular reference to MTN Limited (a giant Telecom Firm in Nigeria). Primary data were collected through questionnaire using quota sampling technique to divide Lagos (sampling population) State to 5 divisions. 50 subscribers were randomly selected from each division to have a total of 250 respondents. 100 members of staff of MTN were equally randomly selected as respondents. Secondary data were obtained from the National Communication Commission (NCC) and MTN Annual Report and Accounts. Multiple Regression, ANOVA and graphical charts were used to analyze the collated data and test the hypotheses. The findings showed that the coefficients of all the results (R2 0.955, F-Test 1531.979 for hypothesis 1); (R20.817, F-Test 324.973 for hypothesis 2); (R2 0.872, F-Test 497.814 for hypothesis 3); and (R20.892, F-Test 603.547 for hypothesis 4) were significant at 0.05 level, meaning that, good ethical CSR practices, environmental CSR, appropriate delivery of societal focused CSR and economic empowerment of the host community have significant effects on organizational performance of the GSM firms. Based on the findings, the authors recommended that, GSM service providers should ensure that they improve on their quality of services, identify the developmental needs of the host communities, abide with the ethical requirement on CSRs, establish peaceful and cordial relationship with the host communities and ensure transparency and prudent use of funds allocated for CSRs since the study has discovered that, there exists a very strong relationship between CSR and firms’ competitive performance.